Voices from the Margin: The Cultural and Social Dimensions of Disability in Leroy F. Moore’s “Buried Voices” - Poudel, Uttam (Mindscape: A Journal of English & Cultural Studies, 2024)
This paper explores the cultural and social dimensions of disability in Leroy Moore’s poem, “Buried Voices.” Throughout the poem, Moore unpacks the marginalized voices of people with disabilities while exposing the challenges they face within familial, social, and political contexts. By invoking Tom Shakespeare’s critical realist approach, which critiques the social model of disability for neglecting the personal experiences and realities of living with impairments, this paper argues that Moore’s poem works as a rallying cry for equality and justice for people with disabilities worldwide. This study employs Robert McRuer’s Crip theory to explore how social norms and discrimination shape the lives of people with disabilities. It also draws on Giorgio Agamben’s concept of “homo sacer” to highlight how their exclusion operates as structural violence, undermining fundamental human rights.The paper further concerns that the maltreatment, exclusion, and marginalization of people with disabilities across various aspects of life constitute a form of structural violence that violates their human rights. Therefore, it is essential to hear their voices and integrate them into familial, social, and political frameworks rather than merely offering sympathy and charity. This paper makes a significant contribution by not only bringing the issues faced by people with disabilities into the limelight through critical discussion but also advocating for their inclusion in key institutions-family, society and politics.